PENGARUH STRATEGI PEMASARAN TERHADAP PENINGKATAN PENJUALAN PADA PERUSAHAANâ DENGAN MENETAPKAN ALUMNI DAN MAHASISWA UNIVERSITAS BINA NUSANTARA SEBAGAI OBJEK PENELITIAN - Hartono, Hendry; Hutomo, Karyana; Mayangsari, Marshelia (Binus Business Review, 2012)
With more advanced technology in the era of globalization, every company strives to always improve the quality of its production and marketing management with the goal of maximizing the benefits of appropriate targets desired by each company. Marketing is one very important function within the company, which with the right marketing can determine the sales volume and position of the company (product) in the market. By analyzing the survey results with the review and assessment activities based on the theories that exist in the literature that has been collected, the respondents considered important to the companys use of marketing strategies that companies can develop and run well in line with current technology.Â